Strategies for Translating Vietnamese Culture-specific Terms in Tourism Materials into English - Tran, Khanh-Ngoc N.; Nguyen, Vu-Khanh; Vo, Lien-Huong (English Department, Faculty of Humanities, Andalas University, 2024)
Tourism plays a crucial role in economic growth, especially in countries which boast rich cultural and natural attractions like Vietnam. With the development of the tourism sector, the role of tourism materials is increasingly pivotal in building destination image and attracting more visitors. The rise of international tourism further necessitates high-quality translation of tourism materials to reach a wider audience. Culture-specific terms (CSTs), which are prevalent in the language of tourism, need to be carefully rendered into the target language to effectively convey the persuasiveness of this genre. On this basis, this study is undertaken to explore the strategies used to translate Vietnamese CSTs into English in tourism materials, particularly an online article. To fulfill this objective, the research employs a mixed method design with a corpus extracted from the online article. Qualitative analysis is applied to identify the translation strategies based on Newmark’s (1988) procedures to translate culture, while the frequency of each strategy is counted for quantitative proceedings. Results indicate that among all the individual strategies, Transference is the most prevalent, followed by Synonymy, Functional equivalent, Cultural equivalent, Adaptation and Through-translation. The most common couplets also involve Transference in combination with other strategies. Besides, detailed analysis shows that there are losses of cultural elements during the translation process, calling for increased attention to the transfer of cultural elements in general and translation of tourism materials in particular. The findings further encourage the development of both linguistic and cultural competences among translators to improve the overall quality of tourism translation.